Engine operating regimes: A propulsion performance study for low-speed two-stroke marine engines - Acomi, Nicoleta; Chervinskyi, Mykyta; Scurtu, Ionut Cristian (Technium: Romanian Journal of Applied Sciences and Technology, 2026)
Understanding the operating regimes of marine engines is essential for evaluating propulsion performance, operational safety, and efficiency in navigation. Although manufacturer load diagrams define the admissible operating envelope, real operating conditions frequently deviate from design assumptions due to resistance growth, environmental influences, and transient manoeuvring events. This study proposes a regime-based analytical framework for assessing propulsion performance in relation to the manufacturer-defined load diagram. The analysis is conducted through a case study of a 31,000 DWT multi-purpose container vessel equipped with a Wärtsilä 6RT-flex58T-D low-speed two-stroke marine diesel engine. Certified sea trial reports and endurance test records provide the primary dataset. Measured propulsion parameters are mapped onto the manufacturer load diagram to evaluate operating-point migration and associated performance implications. The results demonstrate that regime-induced migration of the operating point affects mechanical margin, air-supply availability, and thermal loading. Heavy-running conditions increase torque demand and move the operating point toward low-speed torque constraints, while transient regimes reveal limitations associated with turbocharger inertia and dynamic air–fuel imbalance. The proposed framework integrates manufacturer operating constraints with empirical sea-trial evidence to provide a structured approach for analysing marine engine performance under realistic operational conditions and supporting improved assessment of propulsion efficiency and operational margins.